2005
DOI: 10.1001/jama.293.23.2884
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Supplementation and Risk of Ventricular Tachycardia and Ventricular Fibrillation in Patients With Implantable Defibrillators

Abstract: INCE THE ORIGINAL OBSERVAtions that Greenland Eskimos eating a diet high in omega-3 polyunsaturated fats (PUFAs) from sea mammals and fish had an unexpectedly low risk of cardiac death, 1,2 multiple lines of evidence have suggested that omega-3 PUFAs have antiarrhythmic properties. Four randomized clinical trials 3-6 have shown that dietary changes or supplements to increase omega-3 PUFA intake result in a reduced risk of sudden death without a consistent change in risk of myocardial infarction. To test the hy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(103 citation statements)
references
References 27 publications
(21 reference statements)
2
95
0
4
Order By: Relevance
“…Finally, in a recent trial conducted in patients with implantable cardiac defibrillator, Leaf reported a 40% reduction of recurrent ventricular arrhythmias following fish oil capsules in a double blinded trial 30 . It is noteworthy, however, that in another recent publication reporting fish oil supplementation in the same type of patients, the results were negative 31 . Beside major technical limitations (too small sample size resulting in randomised groups not well balanced for some baseline risk factors and under-powered statistical analyses) especially in one trial with only 200 patients 31 , there is no clear explanation for that discrepancy between trials.…”
Section: Fish Oil and Mediterranean Dietmentioning
confidence: 81%
See 1 more Smart Citation
“…Finally, in a recent trial conducted in patients with implantable cardiac defibrillator, Leaf reported a 40% reduction of recurrent ventricular arrhythmias following fish oil capsules in a double blinded trial 30 . It is noteworthy, however, that in another recent publication reporting fish oil supplementation in the same type of patients, the results were negative 31 . Beside major technical limitations (too small sample size resulting in randomised groups not well balanced for some baseline risk factors and under-powered statistical analyses) especially in one trial with only 200 patients 31 , there is no clear explanation for that discrepancy between trials.…”
Section: Fish Oil and Mediterranean Dietmentioning
confidence: 81%
“…It is noteworthy, however, that in another recent publication reporting fish oil supplementation in the same type of patients, the results were negative 31 . Beside major technical limitations (too small sample size resulting in randomised groups not well balanced for some baseline risk factors and under-powered statistical analyses) especially in one trial with only 200 patients 31 , there is no clear explanation for that discrepancy between trials. Obviously, some major dietary confounders (background marine and plant omega-3 fatty acid intake, omega-6 fatty acid intake, trans fatty acid intake, saturated fatty acid intake), which could greatly interfere with the omega-3 fatty acids given with the capsules, were curiously not measured in these trials and not included (for minimal adjustments) in the calculations of the risks.…”
Section: Fish Oil and Mediterranean Dietmentioning
confidence: 81%
“…However contrasting results have been reported in patients with implantable cardioverter defibrillators [24][25][26] and it is possible that n-3 FA increase risk of re-entrant tachycardia in a small and specific subset of individuals with a slow re-entrant arrhythmic loop around a region of scarred myocardium [23].…”
Section: Biological Effects Of N-3 Fa Related To Cvdmentioning
confidence: 95%
“…However, in Kowey et al's trial [37] of 663 AF patients, omega-3 supplementation did not reduce the recurrence of AF in the 6 month study period. Others have described trends towards reduction in malignant ventricular arrhythmias with omega-3 supplementation [10, [38][39][40]. Although omega-3 fatty acids appear to be effective for reducing SCD in the setting of CHD with reduced left ventricular systolic function [41], 3 trials using omega-3 fatty acids in implantable cardioverter defibrillator patients have shown mixed results [38][39][40].…”
Section: Evidence In CV Diseasementioning
confidence: 99%
“…Others have described trends towards reduction in malignant ventricular arrhythmias with omega-3 supplementation [10, [38][39][40]. Although omega-3 fatty acids appear to be effective for reducing SCD in the setting of CHD with reduced left ventricular systolic function [41], 3 trials using omega-3 fatty acids in implantable cardioverter defibrillator patients have shown mixed results [38][39][40]. The most recent trial evaluating major arrhythmic events was a substudy of the GISSI Heart Failure (HF) trial that showed fewer events in the omega-3 arm, but this finding was not statistically significant [42].…”
Section: Evidence In CV Diseasementioning
confidence: 99%